2013
DOI: 10.1097/scs.0b013e31829042c2
|View full text |Cite
|
Sign up to set email alerts
|

Zygomatico-Orbital Artery as a Recipient Vessel for Microsurgical Head and Neck Reconstruction

Abstract: The selection of recipient vessels in head and neck reconstruction is one of the key factors influencing its difficulty and outcome. We report a case of a microsurgical scalp reconstruction using the zygomatico-orbital artery as a recipient vessel.A 71-year-old woman had intractable skin ulcers on her head after neurosurgeries. Computed tomography angiography findings showed that the superficial temporal artery was obstructed and that the zygomatico-orbital artery ran forward and upward. She underwent scalp re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The ZOA can be used in flap design or as a candidate supply vessel. 12 Previously, ZOA-based flap surgery was difficult because of a lack of understanding of the ZOA's anatomical process. 3 Our research provides an anatomical reference for such operations, and three-dimensionally reconstructed images show that the ZOA originating from the main trunk of the STA provides a rich blood supply to the temporal area.…”
Section: Discussionmentioning
confidence: 99%
“…The ZOA can be used in flap design or as a candidate supply vessel. 12 Previously, ZOA-based flap surgery was difficult because of a lack of understanding of the ZOA's anatomical process. 3 Our research provides an anatomical reference for such operations, and three-dimensionally reconstructed images show that the ZOA originating from the main trunk of the STA provides a rich blood supply to the temporal area.…”
Section: Discussionmentioning
confidence: 99%
“…A few surgical cases used the ZOA instead of the STA 5 . There have also been 2 clinical cases: (1) a forehead ZOA-based island flap used to reconstruct the lower third of the face and (2) the ZOA used as the recipient artery for a flap 5,12 . In the circumstance of a ruptured STA, the ZOA was used for treating a scalp defect, and it was successful result of the forehead for flap construction 12 .…”
Section: Discussionmentioning
confidence: 99%
“…5 There have also been 2 clinical cases: (1) a forehead ZOA-based island flap used to reconstruct the lower third of the face and (2) the ZOA used as the recipient artery for a flap. 5,12 In the circumstance of a ruptured STA, the ZOA was used for treating a scalp defect, and it was successful result of the forehead for flap construction. 12 These cases have demonstrated that the ability to utilize a parieto-occipital flap could depend on the anatomic features of this area, including of the ZOA.…”
Section: Clinical Importance Of the Zygomatico-orbital Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…I read with interest the article by Liu et al entitled “Topographic Anatomy of the Zygomatico-Orbital Artery: Implications for Improving the Safety of Temporal Augmentation.” 1 It provides information on the anatomy of the zygomatico-orbital artery, which can be an option as a recipient vessel in head and neck reconstruction, as Higashino et al pointed out. 2…”
mentioning
confidence: 99%